A commentary on "construction contracts' part II of the Housing Grants, Construction and Regenation Act 1996 - Joyce, Raymond (Thomas Telford, 1996)
This Housing Grants, Construction and Regeneration Act 1996, which received Royal Assent during July 1996, will fundamentally change the way in which construction contracts are to administered and managed. Part 2 of the Act, which seeks to regulate the agreements entered into by parties involved with construction projects, raises many questions for anyone responsible for construction contracts: not least "what is a construction contract?". This book presents a section by section commentary and critical review of Part 2 of the Act. It identifies the main provisions and highlights the difficult issues to be addressed when negotiating, drafting and administering construction contracts.